Amino Acid Profiles, Total Nitrogen Contents, and Computed-Protein Efficiency Ratios of Manihot esculenta Root and Dioscorea rotundata Tuber Peels. (17th November 2016) - Chikezie, Paul Chidoka; Ibegbulem, Chiedozie Onyejiaka; Monago, Odinakachi Stella; Mbagwu, Ferdinand Nkem; Nwachukwu, Chibuike Udodi
Abstract : Tuberous roots of cassava and yam are major sources of dietary carbohydrate to human, alternative sources of energy in livestock feeds, and sources of starch in small-scale industries. Investigations on amino acid profiles, total nitrogen contents, and computed-protein efficiency ratios (C-PER) of tuberous root peels of Manihot esculenta Crantz and Dioscorea rotundata Poir. were carried out. Amino acid analysis was carried out using ion-exchange chromatography methods. Total nitrogen content was measured using the micro-Kjeldahl methods. The C-PER was calculated using regression equation. The concentrations of amino acids detected in the cassava peels ranged from 0.54 to 6.54 g/100 g protein, whereas those of yam peels were between 0.37 and 6.25 g/100 g protein. The total amino acid concentration of the cassava peels was not significantly (p > 0.05 ) higher than that of the yam peels. Essential amino acid scores showed that Phe + Tyr and Met + Cys were the most abundant and limiting amino acids, respectively, in cassava and yam peels. The percentage nitrogen content and C-PER of the cassava peels were significantly (p < 0.05 ) higher than those of the yam peels. The cassava and yam peels were not sources of good quality proteins. Therefore, the use of cassava or yam peels as livestock feeds should be supplemented with other sources rich in good quality proteins.